Na2S2O8‐Promoted Radical Cyclization for the Synthesis of Azaspiro[4.5]deca‐3, 6, 9‐triene‐2, 8‐dione and Pyrrolo[2, 1‐j]quinolone Derivatives. Issue 16 (27th April 2017) - Reddy, C. Ravikumar; Yarlagadda, Suresh; Ramesh, Boora; Reddy, M. Rajashekhar; Sridhar, B.; Reddy, B. V. Subba
Abstract : An efficient radical cyclization of N ‐(4‐methoxyphenyl)‐ N ‐methyl‐3‐phenylpropiolamides with 1‐phenylcyclopropan‐1‐ols has been developed using Na2 S2 O8 to produce azaspiro[4.5]deca‐3, 6, 9‐triene‐2, 8‐diones in good yields with high selectivity. Similarly, the reaction of 1‐[6‐methoxy‐3, 4‐dihydroquinolin‐1(2 H )‐yl]‐3‐phenylprop‐2‐yn‐1‐ones with 1‐phenylcyclopropan‐1‐ols provides 6, 7‐dihydro‐3 H ‐pyrrolo[2, 1‐ j ]quinoline‐3, 9(5 H )‐dione derivatives. This is the first report on the use of cyclopropanols for the radical cyclization of N ‐(4‐methoxyphenyl)‐ N ‐methyl‐3‐phenylpropiolamides and 1‐[6‐methoxy‐3, 4‐dihydroquinolin‐1(2 H )‐yl]‐3‐phenylprop‐2‐yn‐1‐ones. Abstract : An efficient radical cyclization of N ‐(4‐methoxyphenyl)‐ N ‐methyl‐3‐phenylpropiolamides with 1‐phenylcyclopropan‐1‐ols has been achieved using Na2 S2 O8 to produce azaspiro[4.5]deca‐3, 6, 9‐triene‐2, 8‐diones. Similarly, the reaction of 1‐[6‐methoxy‐3, 4‐dihydroquinolin‐1(2 H )‐yl]‐3‐phenylprop‐2‐yn‐1‐ones with 1‐phenylcyclopropan‐1‐ols gives 6, 7‐dihydro‐3 H ‐pyrrolo[2, 1‐ j ]quinoline‐3, 9(5 H )‐diones.